Optimal gestational age at delivery in isolated left‐sided congenital diaphragmatic hernia. (10th May 2021) - Bouchghoul, H.; Dumery, G.; Russo, F. M.; Cordier, A. G.; Le Sache, N.; Debeer, A.; Decaluwe, H.; Fouquet, V.; Senat, M. V.; Deprest, J.; Benachi, A.
ABSTRACT: Objective: To evaluate the morbidity and mortality of neonates with left‐sided isolated congenital diaphragmatic hernia (CDH) according to gestational age at delivery. Methods: This was a retrospective study of fetuses diagnosed prenatally with isolated left‐sided CDH that were delivered in the University Hospitals of Antoine Béclère‐Bicêtre and Leuven between 1 January 2010 and 31 December 2018. The Kaplan–Meier method was used to calculate cumulative survival at 28 days after birth according to gestational age at delivery. The association between gestational age at delivery, as a continuous variable, and survival at 28 days was modeled using a fractional polynomial. Adjustment for position of the liver, management center and mode of delivery was performed. The association was also evaluated according to the severity of CDH, as defined by the observed‐to‐expected lung‐to‐head ratio (o/e‐LHR), which was classified as severe (o/e‐LHR < 25%), moderate (o/e‐LHR between 25% and 45%) or mild (o/e‐LHR > 45%). Results: We included 213 fetuses with isolated left‐sided CDH, with a median gestational age at delivery of 38 + 2 weeks (interquartile range, 37 + 0 to 39 + 1 weeks). The survival rates at 28 days and at 6 months were 66.7% (142/213) and 64.3% (137/213), respectively. Kaplan–Meier analysis showed a higher survival rate at 28 days for babies delivered between 37 + 0 and 38 + 6 weeks than for those delivered at or after 39 + 0 weeks (log‐rank test, P < 0.001). In the subgroup of moderate CDH, the 28‐day survival rate was significantly higher in newborns delivered between 37 + 0 and 38 + 6 weeks than in those delivered at or after 39 + 0 weeks (81.5% vs 61.5%; P = 0.03), and this was also the case for survival rate at 6 months. In the subgroup with moderate CDH, 28‐day survival significantly increased with advancing gestational age at birth up to about 38–39 weeks ( P = 0.005), and significantly decreased from 39 weeks onwards. Conclusion: Delivery between 37 + 0 and 38 + 6 weeks' gestation is associated with a higher survival rate at 28 days in neonates with isolated left‐sided CDH and moderate lung hypoplasia, independently of intrathoracic liver, management center and mode of delivery. © 2020 International Society of Ultrasound in Obstetrics and Gynecology